PELAKSANAAN PEMBERIAN BANTUAN HUKUM TERHADAP ANAK PELAKU TINDAK PIDANA PADA TINGKAT PENYIDIKAN DI KEPOLISIAN RESOR KOTA PEKANBARU - LESTARI, WIWIT; Artina, Dessy; Ferawati, Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Efforts to protect children must be started as early as possible, so that one day they can participate optimally for the development of the nation and state, one way that can be done to provide protection for children is by providing legal assistance to children who commit criminal acts. The implementation of providing legal aid is basically a process when the investigator conducts an investigation process, and the investigator notifies the suspect's right to get assistance at the beginning of the examination in accordance with applicable regulations. Therefore, the purpose of this thesis is: first, to find out the implementation of providing legal assistance to child perpetrators of crime at the level of investigation in the Pekanbaru City Police Force; Secondly, to find out the legal consequences of not providing legal assistance to child offenders at the level of investigation at the Pekanbaru City Police Department.This type of research used in this study is the sociological law meaning research obtained directly from the community or primary data research. Sources of data used, namely: primary data, secondary data and tertiary data. Data collection techniques, namely interviews and literature studies, as well as this study were analyzed using qualitative analysis.The conclusion that can be obtained from the results of the first research, the implementation of providing legal assistance to children perpetrators of crime at the level of investigation in Pekanbaru City Police in practice has not been carried out properly, not in accordance with the mandate of Article 114 of the Criminal Procedure Code and the mandate of the Law Law of the Republic of Indonesia Number 11 Year 2012 Child Criminal Justice System that that every child who commits a crime at every level of the examination must be given legal assistance. Secondly, due to the law not providing legal assistance to children who commit criminal acts at the level of investigation in the Pekanbaru City Police Department is causing defects in the enforcement of the criminal procedure law. Suggestions are expected for the future in handling criminal cases committed by children as investigators are expected to have interest, attention, dedication, and understand the problems of children. Providing legal assistance needs to be carried out in addition to complying with the mandate of the law also considering that children are not adults who have been able to take responsibility for their actions and conduct socialization regarding legal assistance to children who commit crimes, so that all communities and especially parents know that convicted children have the right to get free legal assistance.Keywords: Providing Legal Aid - Perpetrators of Crimes-Pekanbaru